Clinical outcome of COVID-19 in patients with adult congenital heart disease. Issue 15 (8th March 2021) - Schwerzmann, Markus; Ruperti-Repilado, Francisco Javier; Baumgartner, Helmut; Bouma, Berto; Bouchardy, Judith; Budts, Werner; Campens, Laurence; Chessa, Massimo; del Cerro Marin, Maria Jesús; Gabriel, Harald; Gallego, Pastora; Garcia-Orta, Rocio; et al.
Abstract : Aims: Patients with adult congenital heart disease (ACHD) are a potentially vulnerable patient cohort in case of COVID-19. Some cardiac defects may be associated with a poor COVID-19 outcome. Risk estimation in ACHD is currently based on expert opinion. The aim of this study was to collect clinical outcome data and to identify risk factors for a complicated course of COVID-19 in patients with ACHD. Methods: Twenty-five ACHD centres in nine European countries participated in the study. Consecutive patients with ACHD diagnosed with COVID-19 presenting to one of the participating centres between 27 March and 6 June 2020 were included. A complicated disease course was defined as hospitalisation for COVID-19 requiring non-invasive or invasive ventilation and/or inotropic support, or a fatal outcome. Results: Of 105 patients with a mean age of 38±13 years (58% women), 13 had a complicated disease course, of whom 5 died. In univariable analysis, age (OR 1.3, 95% CI 1.1 to 1.7, per 5 years), ≥2 comorbidities (OR 7.1, 95% CI 2.1 to 24.5), body mass index of >25 kg/m 2 (OR 7.2, 95% CI 1.9 to 28.3) and cyanotic heart disease (OR 13.2, 95% CI 2.5 to 68.4) were associated with a complicated disease course. In a multivariable logistic regression model, cyanotic heart disease was the most important predictor (OR 60.0, 95% CI 7.6 to 474.0). Conclusions: Among patients with ACHD, general risk factors (age, obesity and multiple comorbidities) are associated with an increased risk of complicated COVID-19 course. Congenital cardiac defects at particularly high risk were cyanotic lesions, including unrepaired cyanotic defects or Eisenmenger syndrome.